2022
DOI: 10.1093/g3journal/jkac053
|View full text |Cite
|
Sign up to set email alerts
|

The genome organization of Neurospora crassa at high resolution uncovers principles of fungal chromosome topology

Abstract: The eukaryotic genome must be precisely organized for its proper function, as genome topology impacts transcriptional regulation, cell division, replication, and repair, among other essential processes. Disruptions to human genome topology can lead to diseases, including cancer. The advent of chromosome conformation capture with high-throughput sequencing (Hi-C) to assess genome organization has revolutionized the study of nuclear genome topology; Hi-C has elucidated numerous genomic structures, including chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(110 citation statements)
references
References 98 publications
0
110
0
Order By: Relevance
“…However, orphan- het gene clusters and their neighbor genes were syntenic mainly within very closely related taxa, and many orphan genes exhibited no expression under common laboratory settings—even across a range of nutrient conditions and developmental stages. Interestingly, heterochromatic interactions of intra- and inter-telomeric contacts were reported as common in N. crassa (Rodriguez et al 2022), implying potential cis- and trans- regulation at chromosomal level of expression integration in these orphan-gene enriched regions. It is possible that integrating orphan- het gene clusters into existing regulatory systems temporally and spatially modifies the original functions that are expected only under common growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, orphan- het gene clusters and their neighbor genes were syntenic mainly within very closely related taxa, and many orphan genes exhibited no expression under common laboratory settings—even across a range of nutrient conditions and developmental stages. Interestingly, heterochromatic interactions of intra- and inter-telomeric contacts were reported as common in N. crassa (Rodriguez et al 2022), implying potential cis- and trans- regulation at chromosomal level of expression integration in these orphan-gene enriched regions. It is possible that integrating orphan- het gene clusters into existing regulatory systems temporally and spatially modifies the original functions that are expected only under common growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Initially limited to the context of viewing biomolecules (nanoscale), visualization software was thus extended to representation of the 3D organization of chromosomes at the mesoscale. Surprisingly, recent Hi-C studies on S. cerevisiae, S. pombe and N. crassa do not feature 3D models (Rodriguez et al 2022;Tanizawa et al 2017;Costantino et al 2020). In a context where i) an increasing number of Hi-C studies are generated, ii) methods for 3D modeling of Hi-C contacts exist and iii) software for 3D visualization is routinely available in structural biology, one may wonder why contact maps are not associated with 3D models more often.…”
Section: Introductionmentioning
confidence: 92%
“…In 2016, Galazka et al (Galazka et al 2016) identified an inversion of the contig named "12.304", corresponding to a large region in chromosome 6. In 2022, Rodriguez et al (Rodriguez et al 2022) further improved the original assembly "nc12" based on Hi-C data analysis. The updated assembly that integrates the improvements of Galazka et al and Rodriguez et al is available in the GEO database under the accession "assembly nc14".…”
Section: Additional Benefits Of Using 3dgbmentioning
confidence: 99%
See 2 more Smart Citations